Factory through the ages - Steele, Philip, 1948-; Lapper, Ivan; Howett, Andrew; Davidson, Gordon (Mahwah, N.J. : Troll Associates, 1992)
Traces the development of manufacturing in Europe from the simple process of making axes in ancient times to the sophisticated factories that exist today.
Booklist
Horn Book Magazine
5.9
3-6
Keywords: Factory system -- History -- Juvenile literature; Factories -- History -- Juvenile literature; Labor -- History -- Juvenile literature; Working class -- History -- Juvenile literature; Factories -- History; Manufactures; Factories -- History; Manufactures